(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
The study was designed to find out the factors associated with incomplete vaccination of children under five years in secondary healthcare settings of Bahawalnagar, Pakistan. We took a mixed-methods design where structured survey data were combined with qualitative findings from in depth interviews and focus group discussions. The study was comprised of 300 children, indicating that all were fully vaccinated (49.0%); partially vaccinated (37.0%) and not-vaccinated (14.0%). Maternal education, maternal age, family income and distance from health facilities were found to be the significant socio-demographic determinants for immunization status. Following interviews and group discussions, major determinants of incomplete immunization were found to be demand-side barriers (low awareness levels among parents/caregivers inhibition due to misconceptions about vaccines limited understanding level associated with cultural beliefs influencing community acceptance concerns regarding vaccine safety lack-of-Seel/and fear) supply side barriers [poor healthcare worker performance (communication skills missed opportunities storage preventable deaths logistics not following guidelines). oblique challenges data unreliability]/who/Rate issues homelessness etc. Comparison with previous studies showed similar barriers elsewhere, suggesting the necessity to implement targeted public health interventions. The study further recommends community-based education, healthcare delivery and unique strategies for boosting immunization coverage to lower the incidence of vaccine-preventable diseases.